Materiam superabat opus: Lucretius Metamorphosed*. (November 2014) - Schiesaro, Alessandro
Abstract Ovid's narrative of Phaethon's failed attempt prematurely to emulate his father in his unique expertise can be read as a reflection on the virtues and limits of Lucretius' philosophical poetry. The paper suggests that, while he gives much credit to the De Rerum Natura's literary quality and its striving for the sublime, Ovid also critiques the hubristic connotations of Lucretius' rejection of divine authority and agency from the workings of nature. The second part of the article explores how this particular version of the myth touches upon issues of poetic authority, political positioning, and Oedipal competition.